Coparenting and children’s socio-emotional ability: the mediating role of parental stimulation - Wang, Xuena; Huang, Zhongqin; Zhong, Jun; Wang, Suqing; Yu, Liping (Frontiers in Psychology, 2025)
BackgroundPrevious research has inadequately examined the interconnections among coparenting, parental stimulation, and children’s social–emotional ability within the context of Chinese culture.AimConsequently, this study, guided by the coparenting ecological model framework, aims to investigate these relationships and to determine whether parental stimulation serves as a mediating factor.MethodsIn this study, 330 mothers of children aged 12–36 months were selected in Community Health Service Center from April to October 2021 in Wuhan. The general information questionnaire, the Chinese version of Brief Coparenting Relationship Scale, the Infant and Toddler Social and Emotional Assessment, and the Family Care Indicators were distributed. AMOS 21.0 statistical software was used for mediating effect analysis.ResultsIn terms of social emotion, 10.3% of children had abnormal social emotion. Coparenting, parental stimulation, and children’s social–emotional ability pairwise showed a positive correlation. Parental stimulation mediated the association between coparenting and social–emotional ability (β = 0.011, bootstrap 95% CI = 0.006, 0.018). Paternal stimulation and maternal stimulation played a chain mediating role in the relationship between coparenting and social–emotional ability (β = 0.004, bootstrap 95% CI = 0.002, 0.008).ConclusionChildren’s social–emotional ability may be enhanced through interventions that guide and enhance coparenting and parental stimulation.